LINEAR DIOPHANTINE EQUATIONS AND METHODS FOR THEIR SOLUTION - Karimova Nargiza Mamurkhanovna (Bright Mind Publishing, 2025)
This article is addressed to students covering the topic of ‘first degree Diophantine equations & their solutions’. In the article the main focus is on Diophantine equation solutions via geometric interpretation. The concern for Diophantine equations is clearly bound to human nature – its traces are found in preserved documents over thousands of years. Diophantine equations also give opportunity to solve algebraic problems using integers.
Keywords: cryptography, Diophantine equations, solution, algorithm, integers, selection, equality, unique solution